2011
DOI: 10.1039/c1cp21717h
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface ion distribution and buffer effects during electrochemical reactions

Abstract: The near-surface ion distribution at the solid-liquid interface during the Hydrogen Oxidation Reaction (HOR)/Hydrogen Evolution Reaction (HER) on a rotating platinum disc electrode is demonstrated in this work. The relation between reaction rate, mass transport and the resulting surface pH-value is used to theoretically predict cyclic voltammetry behaviour using only thermodynamic and diffusion data obtained from the literature, which were confirmed by experimental measurements. The effect of buffer addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
218
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(229 citation statements)
references
References 30 publications
(38 reference statements)
11
218
0
Order By: Relevance
“…The interpretation of the influence of pH on the HER current–potential relationship (Figure 6) is still under debate 116, 117, 118, 119, 120. Mayrhofer and co‐workers reported that the Nernst–Planck equation [Eq.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
See 3 more Smart Citations
“…The interpretation of the influence of pH on the HER current–potential relationship (Figure 6) is still under debate 116, 117, 118, 119, 120. Mayrhofer and co‐workers reported that the Nernst–Planck equation [Eq.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…in which K w is the equilibrium constant of water molecule dissociation into/formation from a proton and hydroxide ion 119, 120. Simply, the fact that the calculation based on the Nernst–Planck equation matches with the experimental observation indicates that the thermodynamics and mass transport are solely responsible for the j – E relationship of the HER/HOR when the kinetically facile Pt electrode is used.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 The surface pH should be slightly lower during anodic polarization than at OCP because of the higher rate of production of Mg 2+ , which will hydrolyze to a certain extent, and the lower rate of hydroxide ion formation associated with an expected lower rate of hydrogen evolution. Any pH decrease however, should induce a destabilization of Mg(OH) 2 and cause a disruption of the surface film.…”
mentioning
confidence: 99%